Digital Mathematics Teaching Materials to Improve Student Learning Outcomes - Nurdiah Anggraeni Amir; Nurhikmah H; Farida Febriati (Journal of Education Technology, 2025)
Field observations reveal that teachers and students require flexible, independent, and interactive teaching materials that actively engage students in learning. Unlike conventional digital mathematics materials that are typically static, this study develops digital mathematics teaching materials that integrate sophisticated visual design through Canva with Heyzine's interactive flipbook technology to create immersive learning experiences. The product's primary innovation lies in seamless integration of mathematical content aligned with curriculum's Learning Objectives Flow (ATP), responsive visual design, and interactive flipbook features enabling intuitive navigation resembling physical book reading with comprehensive multimedia capabilities. This research encompasses five objectives: analyzing needs, designing, measuring validity, practicality, and effectiveness. The study employs R&D methodology using the ADDIE model. Research subjects comprised seventh-grade students. Findings demonstrate student needs analysis reached "highly needed" category. The design innovation utilizing Canva-Heyzine combination creates distinctive visual-interactive experience unprecedented in junior high mathematics education, fully aligned with ATP standards. Expert validation yielded exceptional results: content experts (92.5%) and media experts (98.3%) rated materials as highly valid. Practicality assessments achieved "highly practical" category (91%-94%). Effectiveness results from pretest-posttest comparisons showed significant learning improvements with substantially higher effect sizes compared to conventional digital teaching materials. This study's primary contribution establishes a new paradigm in digital mathematics teaching material development, creating optimal engagement through innovative visual-interactive experiences within Indonesia's junior high mathematics education context. Results demonstrate that these digital mathematics teaching materials fulfill validity, practicality, and effectiveness standards for enhancing student learning outcomes.